2017
DOI: 10.5539/ells.v7n4p58
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Culture Adaptation Difference between Chinese and American Advertising Discourses

Abstract: Advertising discourse is a kind of strategic communicative language, and adaptation is often used as an effective strategy by advertisers to publicize the products and lure the customers to buy the advertised products. The study is conducted to compare the differences of culture adaptation in Chinese and American advertising discourse, finding different orientations where Chinese advertising discourses and American ones respectively adapt to the potential customers: 1. Collectivism vs. Individualism in Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In addition, this study also found that advertisements aimed at specific target readers. This complements previous research related to accepting the advertisement's product (Zhu, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, this study also found that advertisements aimed at specific target readers. This complements previous research related to accepting the advertisement's product (Zhu, 2017).…”
Section: Discussionsupporting
confidence: 80%